Biological inoculation and organic amendments as strategies to improve ebony (Caesalpinia ebano) tree-seedling growth at the nursery (2018)
An experiment was established with the aim of evaluating the effects of individual and combined addition of organic amendments and microbial inoculation on ebony (Caesalpilinia ebano) plant growth at nursery. A soil surface sample (0-20 cm) from the city of Medellín, Colombia, was transferred into plastic bags (2 kg/bag) and received three types of previously composted organic amendments (manure from domestic animals –dogs and cats (P)-, plant wastes obtained from tree felling and pruning, and grass cutting (RV) and sewage sludge from the city (B)) in two volumetric proportions (20 and 33%) and inoculum composed by the mycorrhizal fungus Rhizoglomus fasciculatum and the mineral solubilizing fungus Mortierella sp. As a reference an uninoculated-and-unamended control was included in this study. The experimental design was completely random, each treatment had 12 replicates. The results indicated that the addition of organic amendments promoted plant growth significantly. However, these effects depended on the type and dose in favor of RV. On the other hand, the inoculation with microorganisms did not have effect on plant growth. The effects were explained as a function of nutrient availability improvement in the substrate with organic amendments and apparently due to a low mycorrhizal dependence of ebony. This paper supports the alternative use of organic amendment generated in the city for improving plant nutrition and growth in urban silviculture.